Mortality Risk and Bequests - Hurd, Michael D. (Econometrica, 1989)
A lifetime utility model, in which the date of death is uncertain and in which bequests give utility, is analyzed and estimated. The parameter estimates imply that most bequests are accidental, the result of mortality risk, and that the shape of the desired consumption path is sensitive to variations in mortality rates. On average, the elderly in the sample dissave, which is consistent with a life-cycle model in which utility does not depend on bequests. Copyright 1989 by The Econometric Society.